Appropriate Use of Ceftriaxone in the Emergency Department of a Veteran's Health Care System. (December 2017) - Durham, Spencer H.; Wingler, Mary J.; Eiland, Lea S.
Background: Ceftriaxone is a third-generation cephalosporin commonly utilized as an empiric antibiotic treatment option in the emergency department (ED). Overuse can lead to decreased susceptibility and emergence of multidrug-resistant pathogens, increased costs, and unnecessary adverse effects.Objective: The purpose of this project was to determine the appropriateness of ceftriaxone usage in the ED of a veteran's health care system.Methods: This retrospective chart review included all veterans who received at least one dose of ceftriaxone in the ED between June 1, 2014, and June 1, 2015. The primary outcome was the percentage of appropriate ceftriaxone use. Usage appropriateness was determined on a case-by-case basis by examining current published guidelines and local recommendations based on the institutional antibiogram.Results: Ceftriaxone was prescribed for a wide variety of indications and was determined to be inappropriately prescribed in 164 patients (53%). The most common reason for inappropriate prescribing was lack of a first-line indication for ceftriaxone (64%). Only 120 patients (38.5%) exhibited systemic signs of infection based on vital signs and laboratory parameters, and 25 patients (8%) likely did not require antibiotic therapy at all.Conclusions: Ceftriaxone was used inappropriately in more than half of the patients who received the drug in the ED. The literature on the prescribing habits for ceftriaxone is limited in the United States, but these results are similar to studies conducted in other countries. Attempts should be made to educate prescribers on appropriate indications for the use of ceftriaxone.